Spotlight on Innovation : AI Trends with Roger Chen - Chen, Roger (O'Reilly Media, Inc., 2019)
Artificial intelligence can be intimidating. There are complex, sticky challenges of data collection and verification, algorithms and bias, and deploying AI services to production, plus ever-expanding ethical concerns. New trends in hardware, algorithms, tools, and data ecosystems are quickly transforming AI into a must-have for today's organizations. Progress is accelerating, but so are obstacles; a successful, real-world implementation of AI depends on balancing many interdependent concerns. Recorded on March 13, 2019. See the original event page for resources for further learning. Find future live events to attend or watch recordings of other past events . O'Reilly Spotlight explores emerging business and technology topics and ideas through a series of one-hour interactive events. In live conversations, participants share their questions and ideas while hearing the experts' unique perspectives, insights, fears, and predictions for the future. In every edition of Spotlight on Innovation, you'll discover what successful companies have in common and how you can follow their lead with small practical steps to transform your organization and prepare for the Next Economy.